Experimental investigation of the equivalence ratio influence on combustion, performance and exhaust emissions of a dual fuel diesel engine operating on synthetic biogas fuel. (15th November 2017) - Aklouche, F.Z.; Loubar, K.; Bentebbiche, A.; Awad, S.; Tazerout, M.
Highlights: Dual-fuel engine using biogas at fixed energy substitution rate (PES) is examined. Effect of total equivalence ratio (ϕ) was studied in the range 0.35–0.7 at 60% PES. HC, CO, CO2 and NOx were reduced of about 77%, 58%, 14% and 24% respectively. Brake thermal efficiency increased with about 13% as ϕ increased from 0.35 to 0.7. Abstract: In this work, an experimental investigation was conducted to analyze dual fuel (DF) engine operation using synthetic biogas fuel under high load at constant percentage energy substitution rate (PES). The performance, ignition delay, and other combustion characteristics of engines operating in dual fuel mode (biogas/diesel), are compared to the conventional mode. The synthetic biogas, composed of 60% methane and 40% carbon dioxide, is the primary fuel which is blended with the air in the engine inlet manifold, whereas the pilot fuel is diesel. The equivalence ratio (fuel-air) (ϕ) was varied by changing air flow rate while the energy introduced into the engine remained constant for all the examined cases. Combustion analysis showed that with increasing ϕ, the ignition delay tends to become longer and the peak of heat release rate was increased. Furthermore, as ϕ increased from 0.35 to 0.7, HC and CO emissions were reduced by 77% and 58% respectively. The NOx emissions decreased at 60% PES by 24% while the BTE was improved by 13%.